High-performance electrochromic supercapacitor with bimetalilic phosphate and vanadium carbide MXene - Sulaiman, Yusran; Mohammad Khalid, .; Mohd Abdah, Muhammad Amirul Aizat; Mohamad Saidi, Norshahirah; Weng, Pin Wong; Yee, Seng Tan; Numan, Arshid; Walvekar, Rashmi; Mohammad Azlan, Fathihah Nabila; Mustafa, Muhammad Norhaffis (Elsevier BV, 2024)
Electrochromic supercapacitor is an excellent multifunctional energy storage device that has great potential for green building and future cities that match the sustainable development goals (SDG), SDG11 (sustainable cities and communities) and SDG13 (climate action). Remarkably, electrochromic supercapacitors can be reversibly coloured upon small voltage induced, which results in the blocking of visible light and solar irradiation. At the same time, electrochromic supercapacitors can also store charge. However, most electrochromic supercapacitor is bottlenecked by the limited specific capacitance (Csp) or coloration efficiency (CE). Herein, the preparation of a novel bimetallic phosphate combined with vanadium carbide MXene (NCP/V2CTx mixtures) using a versatile microwave technique is presented. Surprisingly, the NCP/V2CTx mixtures yielded noteworthy electrochromic performance, including high CE (104 cm2/C), good optical contrast (30.85 %), fast coloring (10.35 s) and bleaching time (20.36 s) as well as good energy storage performance including remarkable Csp (1313 F/g, 1 mV/s), good specific capacity (Qsp = 656.77 mA h/g, 1 mV/s), high specific power (Psp = 1500 W/kg) and high specific energy (Esp = 9.167 W h/kg). The notable electrochromic and supercapacitor performance of NCP/V2CTx mixtures is anticipated to catalyze advancements in the field, shaping the future evolution of electrochromic supercapacitors.